2021
DOI: 10.3390/antibiotics10060714
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variations in Patterns of Clostridioides difficile Strain Diversity and Antibiotic Resistance in Thailand

Abstract: Clostridioides difficile has been recognized as a life-threatening pathogen that causes enteric diseases, including antibiotic-associated diarrhea and pseudomembranous colitis. The severity of C. difficile infection (CDI) correlates with toxin production and antibiotic resistance of C. difficile. In Thailand, the data addressing ribotypes, toxigenic, and antimicrobial susceptibility profiles of this pathogen are scarce and some of these data sets are limited. In this study, two groups of C. difficile isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Interestingly, as ribotype 017 was the most common in both groups, 18 ribotyping patterns previously unknown were identified in the region. This work provides evidence of temporal changes in CD strains in Thailand [10].…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Interestingly, as ribotype 017 was the most common in both groups, 18 ribotyping patterns previously unknown were identified in the region. This work provides evidence of temporal changes in CD strains in Thailand [10].…”
mentioning
confidence: 65%
“…The report by Wongkuna et al showed data addressing ribotypes, toxigenicity, and antimicrobial susceptibility profiles of two series of CD isolates in Thailand [10]. The authors compared two series of CD isolates, including 50 isolates collected from 2006 to 2009 and 26 isolates collected from 2010 to 2012.…”
mentioning
confidence: 99%
“…In addition, environmental samples were not collected at the same time during the study. Moreover, because C. difficile forms spores, which lead to repeated infection, and the persistence of spores in the environment promotes their transmission, 46 we cannot evaluate these potential transmission sources. Fidaxomicin is associated with improved sustained clinical cure and significantly reduces CDI recurrence compared with vancomycin and recommended by several guidelines.…”
Section: Discussionmentioning
confidence: 99%